Functions of the two adenovirus early E1A proteins and their conserved domains in cell cycle alteration, actin reorganization, and gene activation in rat cells. - Bellett, A J (1989)
Rat embryo cells were infected with adenovirus type 5 mutants that code for only one of the two early E1A proteins, mutants with defects in one of the two conserved regions common to the two proteins, or mutants with defects in the 46-amino-acid region unique to the 289-amino-acid E1A protein. Cells were scored for altered cell cycle progression, disruption of actin stress fibers, and activation of E2A expression. Mutants lacking either E1A protein were able to cause all of these effects; but mutants lacking a 243-amino-acid protein had less effect, and mutants lacking a 289-amino-acid protein much less effect, than wild-type virus. A mutation in any of the three conserved regions caused a defect in each E1A effect. To investigate the reported function of conserved domain 2 in mitosis, we monitored by fluorescence-activated cell sorter the reduction in Hoechst 33342 fluorescence that occurs when cells divide after undergoing a round of DNA replication in 5-bromodeoxyuridine. A smaller percentage of adenovirus-infected cells than mock-infected cells divided within a given period after completing a round of DNA replication. Viruses with mutations in conserved domain 2 were defective for initiation of cellular DNA replication, as were all other E1A mutants we have examined, but had no specific defect in cell division compared with wild-type virus. Thus, although there may be some specialization of function between the two E1A proteins and between their conserved domains, it was not apparent in the aspects of E1A function and the mutants that we examined.